Investigation on the Development of Losartan Potassium Sustained Release Microspheres by Solvent Evaporation Methods - Khairnar, Gokul; Patil, Pritam; Mokale, Vinod; Naik, Jitendra (Micro and Nanosystems, 2015)
The purpose of the present study was to investigate the best suited solvent evaporation method for the development of sustained release Losartan Potassium microspheres using ethyl cellulose polymer. Usually microspheres were prepared by oil-in-water (O/W), water-in-oil-in-water (W/O/W), water-in-oil-in-oil (W/O/O) and oil-in-oil (O/O) solvent evaporation methods. Among these methods, O/W and W/O/W methods were failed to produce the microspheres. Microspheres produced by W/O/O method was less encapsulation efficiency and rapid burst release. From these methods, O/O solvent evaporation method was found best method for the preparation of microspheres. In case of O/O method, yield of microspheres and encapsulation efficiency was higher as compared to other methods. The release of drug in distilled water was sustained (56.64%) up to 12 hours. FT-IR analysis showed no interaction between drug – polymer. The morphology of evaluated microspheres on FE-SEM was found spherical with pores on the surface. In XRD analysis, the crystalline nature of pure Losartan was changed to amorphous in microspheres. From this study it was observed that, a highly water soluble Losartan potassium drug can be loaded in ethyl cellulose sustained release microspheres using O/O solvent evaporation method.
Keywords: microsphere